Total Synthesis of an Atropisomer of the Schisandra Triterpenoid Schiglautone A. (25th October 2018) - Ma, Binjie; Zhao, Yifan; He, Chi; Ding, Hanfeng
Abstract: A diastereoselective approach for the total synthesis of an unusual atropisomer of the Schisandra triterpenoid (±)‐schiglautone A is described. The efficient synthetic strategy features three key transformations: 1) two sequential titanium(III)‐catalyzed radical cyclization/homologation reactions to construct the trans ‐fused [6, 7] bicycle as well as install the quaternary carbons at C10 and C14 with the desired stereochemistry; 2) a Claisen rearrangement followed by a ring‐closing metathesis to forge the strained nine‐membered ring; and 3) a substrate‐controlled Michael addition to enable the introduction of the C17 side‐chain with good diastereoselectivity.